An ultra-broadband flexible conductor backed coplanar waveguide with triangular edges - Xie, Tingting; Gong, Pengwei; Xie, Wen; Chai, Jia; Jiang, He; Liu, Jianchun (Scientific reports, 2025)
This paper proposes an ultra-broadband flexible conductor backed coplanar waveguide with triangular edges (FCBCPW-TE), comprising a conductor-backed coplanar waveguide (CBCPW) and triangular arrays arranged periodically along the edges. The simulation results show that the periodically arranged edge triangles could effectively block leaky waves in the DC-70 GHz frequency range. The design of this flexible transmission line, which propagates TEM mode, is straightforward. Through the optimized design, theoretical analysis, and experimental validation, the measured results show that it has good transmission performance in flat, bent, and twisted states. The measured results show that the insertion loss is less than 0.19 dB/mm from 10 MHz to 70 GHz, and the reflection coefficient is less than − 10 dB. Additionally, the measured group delay per unit length is 4.79 ps-6.18 ps, with a group velocity dispersion less than 1.13 ps 2 /mm. The proposed FCBCPW-TE, characterized by high frequency, miniaturization, and ultra-thin flexibility, holds promising potential for application in ultra-miniature high-speed communication systems.